2001
DOI: 10.1097/00003246-200104000-00043
|View full text |Cite
|
Sign up to set email alerts
|

New bronchoscopic microsample probe to measure the biochemical constituents in epithelial lining fluid of patients with acute respiratory distress syndrome

Abstract: These results suggest that BMS is safe and useful to monitor pulmonary biochemical events in ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 9 publications
1
95
0
Order By: Relevance
“…The BMS probe, recently developed in conjunction with Olympus (Tokyo, Japan), consists of a 1.7-mmdiameter polyethylene outer sheath and an inner fiber rod probe 1.2 mm in diameter and 30 mm in length attached to a stainless steel guide wire 100 cm in length. The BMS procedure has been described in detail previously (16). Briefly, the probe was inserted into the channel and gently advanced.…”
Section: Methodsmentioning
confidence: 99%
“…The BMS probe, recently developed in conjunction with Olympus (Tokyo, Japan), consists of a 1.7-mmdiameter polyethylene outer sheath and an inner fiber rod probe 1.2 mm in diameter and 30 mm in length attached to a stainless steel guide wire 100 cm in length. The BMS procedure has been described in detail previously (16). Briefly, the probe was inserted into the channel and gently advanced.…”
Section: Methodsmentioning
confidence: 99%
“…of bronchial ELF at either a subsegmental or subsubsegmental bronchus [3]. This is in contrast to bronchoalveolar lavage (BAL), which samples two sites of infection, i.e., fluid lining the small airways distal to the point of the wedge of the tip of the bronchoscope (alveolar ELF) and alveolar macrophage (AM).…”
Section: Bronchoscopic Microsampling (Bms) Is a New Technique For Repmentioning
confidence: 99%
“…Bronchial ELF sampling was performed with the BMS probe under bronchoscopy [3,6]. In vitro studies showed that more than 90% recovery could be obtained after 1 mg/l of telithromycin or 2-20 ml of human serum was absorbed to the BMS probe.…”
Section: Bms Under Bronchoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Ishizuka et al have reported that bronchial microsampling (BMS) is a safe and useful technique to monitor pulmonary events, enabling the sequential analyses of biochemical and immunological markers in alveolar epithelial lining fluid (ELF), thereby helping to evaluate their pathophysiological significance at several time points during the progression of ARDS (12). Moreover, an advantage of BMS is its uncomplicated performance, without the use of saline, as opposed to bronchoalveolar lavage (13).…”
Section: Introductionmentioning
confidence: 99%